2004
DOI: 10.1002/art.20496
|View full text |Cite
|
Sign up to set email alerts
|

Release of hyaluronan and hyaladherins (aggrecan G1 domain and link proteins) from articular cartilage exposed to ADAMTS‐4 (aggrecanase 1) or ADAMTS‐5 (aggrecanase 2)

Abstract: Objective. To determine whether aggrecanase (ADAMTS) activities in articular cartilage can directly lead to the release of hyaluronan (HA) and hyaladherins (aggrecan G1 domain and link proteins), as may occur ex vivo during stimulation of cartilage explants with interleukin-1 (IL-1) or retinoic acid or in vivo in synovial joints during aging and joint pathology.Methods. Bovine articular cartilage discs (live or freeze-killed) were cultured in the presence of IL-1 or were incubated in digestion buffer containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 57 publications
(66 reference statements)
1
38
0
Order By: Relevance
“…Because the slow migrating bands have intact G1 domains, we postulate that enzymes other than proteinases might be responsible for the release of these fragments (50,51). We (52) and others (53,54) have detected concomitant release of hyaluronan, link protein, and aggrecan G1 fragments into conditioned medium of cytokine-treated cartilage explant cultures, consistent with the hypothesis that hyaluronidases may contribute to depolymerization of the aggrecan aggregate (51). Our present data confirms previous work suggesting that proteolytic and non-proteolytic mechanisms of degradation proceed together (50,51), and also that the non-proteolytic mechanism(s) may be more responsive to treatment with retinoic acid given the pattern and distribution of the SELE 1279 and FREEE 1467 bands seen in Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Because the slow migrating bands have intact G1 domains, we postulate that enzymes other than proteinases might be responsible for the release of these fragments (50,51). We (52) and others (53,54) have detected concomitant release of hyaluronan, link protein, and aggrecan G1 fragments into conditioned medium of cytokine-treated cartilage explant cultures, consistent with the hypothesis that hyaluronidases may contribute to depolymerization of the aggrecan aggregate (51). Our present data confirms previous work suggesting that proteolytic and non-proteolytic mechanisms of degradation proceed together (50,51), and also that the non-proteolytic mechanism(s) may be more responsive to treatment with retinoic acid given the pattern and distribution of the SELE 1279 and FREEE 1467 bands seen in Fig.…”
Section: Discussionmentioning
confidence: 82%
“…T-2 toxin may dissociate and free HA from aggregating aggrecan, seriously damage aggrecan biological functions, initiate aggrecan degradation process and eventually lead to cartilage degradation. While its biochemical and molecular biological mechanism is not clear to date, previous study indicated that the increasing aggrecanase level in cartilage may be involved (Chockalingam et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, ADAMTS4 and 5 exhibit the most powerful aggrecanase activities Tortorella et al, 1999Tortorella et al, , 2001Rogerson et al, 2008). ADAMTSs and the MMPs reportedly play important roles in the metabolism in the extracellular matrix of the cartilage during the development and the progress of joint diseases (Martel-Pelletier et al, 2001;Arner et al, 2002;Chockalingam et al, 2004;Pásztói et al, 2009). Although ADAMTSs are especially believed to be involved in the cellular growth, differentiation, and maturation of the growth plate chondrocytes, their roles in the endochondral ossification have not been completely elucidated (Demircan et al, 2005;Mitani et al, 2006;Hatipoglu et al, 2009a;Yaykasli et al, 2009).…”
Section: Immunohistochemistrymentioning
confidence: 99%